Reproduction Based on Islamic Culture: Effort to Increase Understanding of Reproduction System and Prevention of Infectious Diseases - Fuadi, Tuti Marjan (SCAD Independent, 2019)
The number of people living with HIV / AIDS in Indonesia is increasing from time to time. Based on the Department of Health report, up to December 2011 there were 27,947 HIV/AIDS sufferers in Indonesia. 1,069 (3.83%) of them were aged 15-19, while 13,053 (46.71 %) were aged 20-29. The age group of 30-39 was 8,832 people (31.60%), age group of 40-49 was 2,840 people (10.16%), age group of50-59 was 83 people (0.30%) and over the age of 60 were 233 people (0.83%) The most sufferers are adolescents and adults. This study aims to examine and link learning culture-based human reproductive system in order to improve understanding of reproduction and prevent reproductive disease. The formulation of the problem in this study is how the application of learning culture-based human reproductive system affects the understanding of reproduction. This research is designed with Quasi Experiment method with One Group Pretest-Postest Design The study was conducted at MAN Darussalam Aceh Besar class XI IPA 1 involving 23 students and five observers and a biology teacher. The results of this study obtained a description of the reproduction system based on culture that affects the improvement of students. It was concluded that the application of learning of human culture based reproduction system has been able to increase students understanding on reproduction. Students can build knowledge through active involvement in the learning process and their understanding of the concept of the human reproductive system is increasing (N-gain = 71%).